Sassenheim en Arnhem: twee benzinestations naar ontwerp van ir. S. van Ravesteyn (1889-1983) (Bulletin KNOB, 1997)
Many buildings of architect Sybold van Ravesteyn (1889-1983) have been demolished by now. Most of Van Ravesteyn's buildings for the Dutch Railway were brutally depleted. In the period between 1935 and 1963 he designed twenty-five petrol stations for oil company Purfina (Fina), of which at the moment only eight have survived.In this article two petrol stations by Van Ravesteyn will be discussed: one petrol station in Sassenheim (from 1951, recently demolished) and one in Arnhem (from 1957, still existing and protected as a listed building on the municipal historic buildings register). On national highway 44 between Amsterdam and The Hague, 1938, there was a small petrol station by Van Ravesteyn near Sassenheim.The building had a minimum of facilities for motorist and pump attendant and was situated at a slight bend in the highway. Because of the soil conditions the architect used concrete upright extensions for the foundations. The design was simple: a ground plan in the form of a stirrup, the straight side with the kiosk directed towards the road and provided with a glass facade, the semicircular rear was closed and contained a few subordinate spaces.Pump attendant and motorists were sheltered by a porch built at the front of the petrol station. Van Ravesteyn used the same design more often, e.g. in Zwammerdam (Reeuwijk) on national highway 12 and in IJsselstein, on national highway 2, but both buildings were overtaken by changing standards or requirements of use and, consequently, demolished and replaced.The petrol station in Arnhem distinguishes itself by its remarkable appearance. It has a narrow, pointed ground plan and a pent-roof. From the lodge in the peak of the petrol station the pump attendant carried out his work. The remarkable architecture was intended to attract the motorist's attention to the petrol station, so that he would stop and fuel up or buy lubricants.It took the architect some trouble to get the striking design through the Urban Aesthetics Committee, but eventually a passionate plea won over conservatism. For several reasons the same design failed to be carried out in Leiden and in Moergestel, whereas in Ede it was executed, but has meanwhile been replaced.In Arnhem municipal conservation of monuments resulted in the preservation of the by now unique petrol station. Petrol stations form a specific category in the history of twentieth-century architecture. The conservation department has difficulties in getting a grip on this category, also because the Monuments and Historic Buildings Act 1988 requires a building to be at least fifty years old, a period of time which hardly ever or never appears to apply to petrol stations.Changing requirements of use, stricter regulations by environmental legislation and rock-hard competition among the oil companies threaten the continued existence of this specific group of industrial buildings which rightly have a symbolic function for the twentieth century.In the light of the increasing interest in and research on the history of industrial and technical monuments, the petrol station deserves greater acknowledgement and appreciation than it received in the past. Here a decisive municipal conservation policy can play a part: a municipal listed buildings order need not be restricted to the said period of at least fifty years. Quick action is required. The twentieth century produced the petrol station but, like Saturn, seems to be consuming its offspring.